Labour Absorption at Various Types of Livestock Business in Banyumas Regency - Djatmiko, OE; Sugiarto, M (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2008)
Â ABSTRACT: The research was aimed to (1) know the level of labour absorption at various types of livestock business, (2) compare labour absorption at various types of livestock business and (3) analyze the influence of business scale, labour productivity and economic efficiency to absorption of labour at various types of livestock business in Banyumas regency. Research was done by using survey method to farmers households. The areas of research were selected using purposive sampling based on number of livestock population in those districts. Respondents were drawn randomly by using simple random sampling method. One way ANOVA was used to test the difference of labour absorption among four types of livestock business. Meanwhile, multiple regression analysis was used to study the influence of business scale, labour productivity and economic efficiency to labour absorption. Research results showed that labour absorption on dairy cattle business was 1.23 STKSP (man equivalent labour unit), sheep was 1.54 STKSP, goat was 1.75 STKSP and beef cattle were 1.14 STKSP. There was a significant difference of labour absorption from four existing types of livestock business. Labour absorption was significantly influenced in positive direction by business scale and economic efficiency of business, while labour productivity has a negative significant influence on labour absorption. (Animal Production 10(3): 198-202 (2008) Â Key Words: Labour, business, livestock